2005
DOI: 10.1002/polb.20573
|View full text |Cite
|
Sign up to set email alerts
|

Conformational variation and crystalline phase transformation of low syndiotactic polypropylene films in stretched and stress‐relaxed states

Abstract: Low syndiotactic polypropylene (sPP; rrrr = 80%) films were isothermally crystallized at 0 °C (sample S0) and 90 °C (sample S90) for 65 h, respectively. Fourier transform infrared spectroscopy, differential scanning calorimetry, and wide‐angle X‐ray diffraction were used to characterize the structure transformation and orientation behavior of samples S0 and S90 at both stretched and stress‐relaxed states. It was found that stretching (λ = 0–700%) induces the transformation of the chain conformation from helica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This is assigned to the fact that all thermodynamic parameters included in eq that govern the crystalline lamellar thickness are related mostly to the mesomorphic and crystalline phase only independent of the state of amorphous phase. Hints of existence of mesomorphic phase in sPP during stretching have been reported extensively. ,, The observed slight increase in the limiting temperature for stretching induced crystallization in sPP can be understood as a result of the influence of global orientation of polymer chains on the thermal dynamic parameters of the mesomorphic phase.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This is assigned to the fact that all thermodynamic parameters included in eq that govern the crystalline lamellar thickness are related mostly to the mesomorphic and crystalline phase only independent of the state of amorphous phase. Hints of existence of mesomorphic phase in sPP during stretching have been reported extensively. ,, The observed slight increase in the limiting temperature for stretching induced crystallization in sPP can be understood as a result of the influence of global orientation of polymer chains on the thermal dynamic parameters of the mesomorphic phase.…”
Section: Resultsmentioning
confidence: 90%
“…Hints of existence of mesomorphic phase in sPP during stretching have been reported extensively. 21,24,25 The observed slight increase in the limiting temperature for stretching induced crystallization in sPP can be understood as a result of the influence of global orientation of polymer chains on the thermal dynamic parameters of the mesomorphic phase.…”
Section: Resultsmentioning
confidence: 99%
“…An in situ X‐ray diffraction study showed that this transition was a fast and direct process, occurring nearly instantaneously as the material was strained . Rheo‐FTIR studies also confirmed the transition …”
Section: Lattice Structure and Conformational Variationmentioning
confidence: 82%
“…The initial structures of S 0 and S 90 films have been described in detail in our previous paper . In brief, the initial structure of sample S 0 consists of form I crystals with a helical conformation and trans-planar mesophase, while sample S 90 allows the prevalent crystallization of form I.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the helical conformation does not orient appreciably at higher temperature, though it is present beyond the yield point, while the trans-planar chains show a significant increase in dichroism. The orientation of different structures is related to the content of structure during stretching, which is controversial compared with other results. , Therefore, this research is not enough to provide comprehensive understanding of the orientation behavior of different structures in sPP and their dependence on the initial morphology and the stretching temperature.…”
Section: Introductionmentioning
confidence: 90%